2023
DOI: 10.21037/jtd-23-192
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of pulmonary sarcoidosis in tuberculosis endemic area—a narrative review

Tulaton Sodsri,
Robert P. Baughman,
Thitiwat Sriprasart

Abstract: Background and Objective Pulmonary sarcoidosis and tuberculosis (TB) are the most frequent tissue-confirmed granulomatous diseases. Due to its unknown etiology, pulmonary sarcoidosis is diagnosed by ruling out other granulomatous diseases and necessitating clinical, radiological, and pathological evidence. There are many factors that contribute to the diagnostic dilemma between these two diseases. Even though some aspects of both diseases, such as their pathological evidence and abnormal X-ray fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…MTB culture, and T lymphocytes γ-Interferon analysis, molecular amplification, etc. [2][3][4][5][6][7][8] In HIV/AIDS populations with immune disorders, samples with low levels of MTB bacteria may limit the validity of traditional etiological diagnosis. The report showed that from 2016 to 2020, the popularization rate of MTB molecular diagnostic technology in 11 prefecture-level city disease prevention and control center laboratories in Hebei Province reached over 90%, but the positive rates of MTB pathogen were below 36.28%.…”
mentioning
confidence: 99%
“…MTB culture, and T lymphocytes γ-Interferon analysis, molecular amplification, etc. [2][3][4][5][6][7][8] In HIV/AIDS populations with immune disorders, samples with low levels of MTB bacteria may limit the validity of traditional etiological diagnosis. The report showed that from 2016 to 2020, the popularization rate of MTB molecular diagnostic technology in 11 prefecture-level city disease prevention and control center laboratories in Hebei Province reached over 90%, but the positive rates of MTB pathogen were below 36.28%.…”
mentioning
confidence: 99%